Experimental measurements of charge separation under wet growth conditions - Luque, Melina Yasmín (2018)
In this work we present the results of experimental measurements of the charge transferred to simulated graupel under wet growth conditions. The range of temperature was between −7 and −18 °C. The speeds of collision employed in the measurements were between 8 and 13 m/s with the goal of representing graupel of different initial densities. The aim of this study was to corroborate the existence of charge transfer under wet growth. The results show the presence of positive charge when graupel reaches partial wet growth, and the magnitude of this charge is comparable to the charge transferred under dry growth conditions. On the other hand, when total wet growth is reached no charge transfer is registered. This leads to the conclusion that the non-inductive mechanism could be working under partial wet growth conditions when the ice crystals collide with the dry regions of the graupel surface and then bounce off.